Hyperprogressive Disease Caused by PD-1 Inhibitors for the Treatment of Pan-Cancer. (22nd June 2021) - Chen, Shiyun; Gou, Miaomiao; Yan, Huan; Fan, Mengjiao; Pan, Yuting; Fan, Runjia; Qian, Niansong; Dai, Guanghai
Abstract : Background . Nowadays, PD-1/PD-L1 inhibitors are widely used to treat various malignant tumors. However, during the immunotherapy in a few patients, a flare-up of tumor growth occurred. This new pattern of progression is called hyperprogressive disease (HPD). Patients and Methods . The retrospective study included 377 patients with various malignant tumors treated with PD-1 inhibitors (nivolumab or pembrolizumab) in the Chinese PLA General Hospital from January 2015 to January 2019. Clinicopathologic variables, tumor growth rate (TGR), and treatment outcomes were analyzed in patients with pan-cancer treated with PD-1 inhibitors. HPD was defined as the difference of TGR before and during immunotherapy exceeding 50%. Results . In 38 of 377 patients (10.08%), HPD occurred after treatment with PD-1 inhibitors. Patients with HPD had lower overall survival (OS) than those without HPD (median OS, 3.6months (95% CI, 3.0–4.2) vs. 7.3 months (95% CI, 5.9–8.7); P < 0.01 ). Factors related to HPD include more than 2 metastatic sites, ECOG performance status ≥ 2, hepatic metastases, and lactate dehydrogenase level greater than normal upper limit. KRAS status was significantly associated with HPD in patients with colorectal cancer. In the exploratory predictors' analysis, the rapid increase of characteristic tumor markers (such as CEA in colorectal cancer, CA199 in pancreatic cancer and cholangiocarcinoma) within one month was found to be associated with the occurrence of HPD. Conclusions . HPD was developed with different rates in a variety of malignant tumor patients treated with PD-1 inhibitors and related to some clinicopathological features and poor prognosis. Tumor markers, especially CA199, might be served as early predictors of HPD.